2007
DOI: 10.1634/stemcells.2006-0637
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoxia Defines Heterogeneity and Selects Highly Immature Progenitors Within Clonal Erythroleukemia Cells

Abstract: We showed that resistance to severe hypoxia defines hierarchical levels within normal hematopoietic populations and that hypoxia modulates the balance between generation of progenitors and maintenance of hematopoietic stem cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Previously, investigators have studied the role of hypoxia in leukemia using relatively shortterm assays. [30][31][32] Our results suggest that transient hypoxia may not adequately mimic the physiological environment of CML cells (Figure 3e). Furthermore, in the mouse CML xenograft model, the oxygen concentration of engrafted leukemic cells in the BM was o10 mm Hg (B1.3% O 2 ) (Figure 1f).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previously, investigators have studied the role of hypoxia in leukemia using relatively shortterm assays. [30][31][32] Our results suggest that transient hypoxia may not adequately mimic the physiological environment of CML cells (Figure 3e). Furthermore, in the mouse CML xenograft model, the oxygen concentration of engrafted leukemic cells in the BM was o10 mm Hg (B1.3% O 2 ) (Figure 1f).…”
Section: Discussionmentioning
confidence: 92%
“…Giuntoli et al 32 have also reported that the hypoxic selection of CML cells resulted in decreased cell sensitivity to imatinib and activation of Bcr-Abl-independent survival signaling pathways. Erk, a downstream effector of Bcr-Abl, was also less phosphorylated in HA-CML cells compared with parental cells, whereas the levels of p-Akt and p-Stat5 were similar (Figure 2f).…”
Section: Discussionmentioning
confidence: 97%
“…1,2 The existence of different, metabolically characterized, functional cell subsets within leukemia cell populations reflects the organization of normal hematopoiesis, where the regulatory role of glycolysis and respiration within the stem/progenitor cell hierarchy has been long known. [3][4][5][6] Such an organization is functional to the maintenance of stem cells within restricted, "metabolically-defined" bone marrow areas which we called the "hypoxic stem cell niches".…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that a compromised blood flow with very low oxygen support could favor the outgrowth and survival of AML clones reducing their exposure to systemic chemotherapy and immune effector cells [79]. This suggestion has been indirectly confirmed by the finding that leukemic cells requiring very low oxygen and energy support correspond to quiescent, chemoresistant and self-renewing leukemic cell subsets [82]. These functionally defined LSCs are completely dependent on mitochondrial respiration to fulfill their low energy requirements as they are unable to employ glycolysis [83].…”
Section: Niche Contribution To Aml Developmentmentioning
confidence: 80%
“…Various studies have demonstrated that LSCs and HSCs might share the same bone marrow niches [25,26,32] and compete for vacant niches as the number of these areas within the BM is limited [29]. Since these malignant niches provide a shelter for LSCs [79,82,83] and also specify their self-renewal properties [10,22,23] an attractive therapeutic strategy could be to dislodge these cells from their niche by targeting the CXCR4/CXCL12 interaction. Xenograft models have already shown that CXCR4-CXCL12 targeting is feasible and could lead to more efficient disease eradication [92,105]; these data have provided the rationale to combine Plerixafor (ADM3100), the principal manipulator of the CXCR4-CXCL12 axis, with conventional chemotherapy (Table II).…”
Section: Potential Targetsmentioning
confidence: 99%